Ownership Strategy in a Public Organization and Responsible Ownership - Jónsdóttir, Guðrún Erla; Steinþórsson, Runólfur Smári; Sigurjónsson, Þröstur Olaf (Research in applied business and economics, 2022)
Ownership strategies of companies and public institutions were established as a significant governance mechanism following the global financial crisis in 2008. The Icelandic government was the first to establish an ownership strategy for its companies in 2009. The goal is that their holding companies are run professionally and transparently. That will establish trust in the management and operations held responsible. The basis of the ownership role is general guidelines on good corporate governance as well as general guidelines on the role and responsibilities of the owners. There has been a growing discussion in recent years about good governance, despite this, there are few sources, in Iceland and elsewhere, about the origin and purpose of an ownership strategy. This article reviews the theoretical foundations of ownership strategy, active and responsible ownership, and the alignment of owners. Based on an empirical study it is explored whether, and how, ownership strategy is theoretically positioned, for a definition of the concept. The results are based on a qualitative study of active ownership, shareholder activity, and responsible ownership. The case study explores the ownership strategy of a specific company, Orkuveita Reykjavíkur, which is owned by three municipalities. The results of the study support the theoretical foundations of ownership strategy and clarify the concept. It is also argued that stakeholders view the restriction on the mandate of the board in a positive way. The study also reveals the positive impact of ownership strategy on board decision-making, as responsible ownership leads to owners placing emphasis on more than mere financial performance, demonstrating ambition towards sustainability and social responsibility. Eigendastefna fyrirtækja og stofnana hefur fengið aukið vægi í kjölfar hrunsins árið 2008. Íslensk stjórnvöld settu fyrst fram eigendastefnu fyrir félög í eigu ríkisins árið 2009. Tilgangurinn var sá að stuðla að því að félög í þeirra eigu væru starfrækt með faglegum og ...